2015
DOI: 10.1371/journal.pone.0122521
|View full text |Cite
|
Sign up to set email alerts
|

Association between Poor Glycemic Control, Impaired Sleep Quality, and Increased Arterial Thickening in Type 2 Diabetic Patients

Abstract: ObjectivePoor sleep quality is an independent predictor of cardiovascular events. However, little is known about the association between glycemic control and objective sleep architecture and its influence on arteriosclerosis in patients with type-2 diabetes mellitus (DM). The present study examined the association of objective sleep architecture with both glycemic control and arteriosclerosis in type-2 DM patients.DesignCross-sectional study in vascular laboratory.MethodsThe subjects were 63 type-2 DM inpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 30 publications
3
62
1
1
Order By: Relevance
“…In the eight studies that examined the linear relationship between sleep duration and glycaemic control, six did not find a significant association. HbA1c or fasting glucose was not related to sleep duration measured by objective EEG (Yoda et al., ), actigraphy (Knutson et al., ; Kwan, ; Trento et al., ), or self‐reported questionnaire (Cho et al., ; Giacinto, ). Only in two studies was the relationship between sleep duration and HbA1c significant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the eight studies that examined the linear relationship between sleep duration and glycaemic control, six did not find a significant association. HbA1c or fasting glucose was not related to sleep duration measured by objective EEG (Yoda et al., ), actigraphy (Knutson et al., ; Kwan, ; Trento et al., ), or self‐reported questionnaire (Cho et al., ; Giacinto, ). Only in two studies was the relationship between sleep duration and HbA1c significant.…”
Section: Resultsmentioning
confidence: 99%
“…Sleep quality has been objectively measured by EEG, polysomnography (PSG) or actigraphy. Objective sleep latency ( r = −.342 to −.292, p < .05) (Yoda et al., ) and sleep efficiency ( r = −.29, p = .047) (Trento et al., ) was negatively correlated with glycaemic control. Greater sleep fragmentation was associated with higher fasting glucose (β = .089, p < .05) (Knutson et al., ) and HbA1c ( r = .31, p = .031) (Trento et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the standard cut-off point to define poor sleep quality (PSQI global score >5). As a proxy for disturbed rapid eye movement (REM) sleep, which has been linked to poor glycemic control in individuals with T1D [24] and type 2 diabetes [31], we defined the presence of bad dreams (any versus none) by utilizing the following PSQI item: “During the past month, how often have you had trouble sleeping because you had bad dreams?” Sleep duration in hours was quantified from PSQI, where participants reported self-perceived duration of actual sleep per night. We also categorized sleep duration by tertiles and by the National Sleep Foundation’s (NSF) [32] adult sleep guidelines (<7 hours=short sleep, 7–9 hours=normal sleep, and >9 hours=long sleep).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, many patients with Type 2 diabetes have insomnia [13]. Analyzing the quality of sleep of hospitalized patients with Type 2 diabetes using electroencephalograph [14], has indicated that if HbA1c increased or worsened, poor glycemic control was independently associated with poor quality of sleep as represented by decrease of REM sleep latency.…”
Section: Introductionmentioning
confidence: 99%